Tsunami Risk Assessment in Business Continuity Planning for Palu Special Economic Zone. Issue 1 (1st July 2022) - Purnama, Muhammad Rizki; Adityawan, Mohammad Bagus; Pribadi, Krishna Suryanto; Farid, Mohammad; Widyaningtias,; Kuntoro, Arno Adi
Abstract: On September 28, 2018, an earthquake with a magnitude of 7.4 Mw struck Central Sulawesi, Indonesia and triggered a major tsunami. At least 3475 people lost their lives as reported by the Indonesian National Board for Disaster Management (BNPB), while a large unknown number is still buried under the rubble and presumed dead. This event also damaged the facilities and infrastructure of the Palu City coastal area. Currently, The Government of Palu is developing the Palu Special Economic Zone (PSEZ) in Tawaeli District, Palu, Central Sulawesi to attract investors and spur economic growth in neighbouring areas. Thus, mitigation plans are urgently needed to reduce damage and losses due to the impact of future tsunamis on PSEZ. This study assesses the impact of tsunamis around the Palu Special Economic Zone and its supporting infrastructure. Hypothetical earthquake-induced tsunamis were simulated using Delft3D and DelftDashboard. The fault scenario is developed based on data from PUSGEN. Further parameters were developed with the empirical earthquake source-scaling laws. The model simulates the tsunami generation, propagation, and inundation from the source to the coastal area. A tsunami impact scenario is then developed as a basis for analysing the business impact to the transportation infrastructure and critical utilities serving the PSEZ, as well as to the operation of the industries and businesses within the PSEZ. The lessons learned from this study can assist stakeholders in developing an areawide business continuity plan as a commitment of the stakeholders for implementing areawide business continuity management for the PSEZ, which will improve the economic resilience of the Palu City as well as South Sulawesi region.